Selves Engraved on Stone: Seals and Identity in the Ancient Near East, ca. 1415-1050 BCE - Yalcin, Serdar (Culture and History of the Ancient Near East, 2022)
Selves Engraved on Stone explores the ways in which multiple aspects of identity were constructed through the material, visual, and textual characteristics of personal seals from ancient Mesopotamia and Syria in the latter half of the 2nd millennium BCE.